Comparison of pain threshold and duration of pain perception in men and women of different ages - Marília Soares Leonel de Nazaré; José Adolfo Menezes Garcia Silva; Marcelo Tavella Navega; Flávia Roberta Fagnello-Navega
Introduction Pain is a sensory and emotional experience that occurs with the presence of tissue injury, actual or potential. Pain is subjective, and its expression is primarily determined by the perceived intensity of the painful sensation, called the pain threshold. Objective To evaluate whether there are differences in pain threshold (LD) and time to pain perception (TPED) between the gender in different age groups and to analyze the correlation between age and pain threshold in each gender. Methods and procedures Participants were 60 volunteers divided into 6 groups (n = 10 each) according to gender and age (18-33, 34-49, and 50-64 years). The evaluation of perception and pain tolerance was performed by immersing the container with one hand in water at a temperature of 0 °C-2 °C; the latency to withdrawal of the hand from ice water was measured in seconds and was considered a measure of LD. The TPED was reported by each participant as the start time of the painful stimulus. Results We found differences between the LD for G1 (men aged between 18 and 33 years) and G2 (women aged 18 to 33 years) with greater LD for G1 (p = 0.0122) and greater LD for women (p = 0.0094); for other comparisons of LD and TPED, there were no differences (p > 0.05 for all comparisons). Low correlation was found between age progression with increased LD and the TPED only in men (p = 0.01 and r = 0.45 and p = 0.05 and r = 0.34, respectively). Conclusion We conclude that women have a higher pain threshold than men especially when these groups are aged between 18 and 33 years, and in men increasing age correlates with increased TPED and LD.